2010
DOI: 10.1007/s12185-010-0699-1
|View full text |Cite
|
Sign up to set email alerts
|

Histiocytic sarcoma with two immunohistopathologically distinct populations

Abstract: This report is a case of histiocytic sarcoma (HS), in which tumor cells consist of two immunohistopathologically distinct populations (A) oval CD68+lysozyme+CD163- cells and (B) abundant cytoplasm or spindle-shaped CD68+lysozyme-CD163+ cells. Cervical lymph node was infiltrated mainly by population (A), where chemotherapy was quite effective. On the other hand, vast majority of infiltrated tumor cells in the hilar lymph node belonged to population (B), in which the cells were resistant to chemo-radiotherapy. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Necrosis was more often seen in FCR than in the BMD and may indicate a higher malignancy/faster growing tumor than in the BMD. Different morphological characteristics in different organs within one case were seen in this study and have been reported before (56). Metastatic tumor cells seem to first disseminate from the early primary lesion and then acquire additional genetic defects and often exhibit properties different from the cells of the primary lesion (57).…”
Section: Discussionsupporting
confidence: 53%
“…Necrosis was more often seen in FCR than in the BMD and may indicate a higher malignancy/faster growing tumor than in the BMD. Different morphological characteristics in different organs within one case were seen in this study and have been reported before (56). Metastatic tumor cells seem to first disseminate from the early primary lesion and then acquire additional genetic defects and often exhibit properties different from the cells of the primary lesion (57).…”
Section: Discussionsupporting
confidence: 53%
“…Although CD68 and CD163 as well as lysozyme were positive in most of the reported HS cases, a lysozyme-negative HS case was also reported. 11 That case had two populations of CD68 + CD163 -lysozyme + oval cells in cervical lymph node and CD68 + CD163 + lysozyme -spindle cells in hilar lymph node. The tumor cells in our case are quite similar to this latter cell component.…”
Section: Discussionmentioning
confidence: 88%
“…HS is difficult to diagnose as its morphological features are highly variable (Affolter & Moore, 2002; Erich et al., 2018; Wakahashi et al., 2010). The morphologic features of HS can often mimic other tumours of mesenchymal or round cell origin such as sarcomas, plasma cell tumour, mast cell tumour, lymphoma, transmissible venereal tumour or amelanotic melanoma.…”
Section: Introductionmentioning
confidence: 99%